Apnea training effects on swimming coordination - Lemaitre, F.; Seifert, L.; Polin, D.; Juge, J.; Tourny-Chollet, C.; Chollet, D. (The Journal of Strength and Conditioning Research, 2009)
Triathletes and elite breath-hold divers show an adaptive response to hypoxia induced by repeated epochs of breath holding. We hypothesized that hypoxic training could also improve swimming coordination. Before and after a 3-month breath-hold training program, 4 male swimmers performed a maximal incremental test on bicycle and a 50-m front crawl race at maximal speed without breathing so that interarm coordination could be assessed. Swim velocity, stroke rate (SR), stroke length (SL), and the arm stroke phases were calculated from video analysis. Arm coordination was quantified in terms of an index of coordination (IdC) based on the time gap between the propulsive phases of each arm. After apnea training, the forced expiratory volume in 1 second was higher (4.85 ± 0.78 vs. 4.94 ± 0.81 L, p < 0.05), with concomitant increases in Vo2peak, minimal arterial oxygen saturation, and respiratory compensation point values (W and W/kg) during the incremental test. Swimming performance was not improved (clean velocity and time on 50 m); however, SR was decreased and SL and IdC were increased. These results indicate that apnea training improves effectiveness at both peak exercise and submaximal exercise and can also improve swimming technique by promoting greater propulsive continuity.